Pendampingan Kerja Praktik Untuk Meningkatkan Ketrampilan Proses IPA Bagi Guru Guru SD Di Kota Mataram - Sutrio; Wahyudi; Ni Nyoman Sri Putu Verawati; Ahmad Busyairi; Ananda Fatara Suwandi; I Wayan Gunada (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
In elementary schools (SD), KIT IPA equipment is used to practice teaching and learning activities that teachers have not used to their full potential. Kit of knowledge and management abilities Teachers require IPA SD to advance their school. The management of KIT IPA is less effective and has become a major issue for elementary schools (SD) Group IV Cakranegara. The goal of this community service activity is to teach people about the names of the tools in some SD IPA KIT IPA SD, how to use them, and how to use KIT IPA SD in the learning process. This devotional activity employs lecture methods, simulations, and practical work. This activity was held in SD Negeri 1 Cakranegara, with as many as 28 teachers participating. The activities' outcomes demonstrated that participants gained knowledge and skills on how to teach IPA by utilizing KIT IPA tools for practical work activities. Based on observations from practical work, the average value of process skills of teachers was 70 and classified quite well. The positive response from teachers in mentoring activities indicates that this activity is running smoothly, and it is expected that there will be additional training for other KIT equipment as a result of this activity.